Konsep Empowerment Sebagai Instrumen Pembangunan Ekonomi Islam (Telaah Kritis Pemikiran Ibnu Khaldun dan Umer Chapra) - Moh. Musfiq Arifqi (Al-Tijary, 2019)
The main problem of economic development such as poverty, unemployment, asymmetry of economic among individuals could not be removed succecfully in Indonesia. One of the reasons is caused with unreadable other variables such as social law, politics, culture and so on. The size of the success Islamic economic growth is not measured only from the material achievement perspective or the results of quantity, but also from the improving religious perspective, social and society life. The motodology of this research is library research. To get more information, the reference is taken from some book that have relation with the topic. The result is that Ibn Khaldun’s thought is referring to the term "umran al-alam" or prospering the world. It is formed from three components, namely; history (tarikh), cooperation among society (al-ijtima 'al-insani) and the universe (al-kawn). Ibnu Khaldun offered the concept of Islamic economic development: First, the contribution of humans (ar-Rijal). Second, the contribution of development (al-Imarah), Third, the contribution of institutions and government. Fourth, the contribution of wealth (al-mal). Umer Chapra believed that the means of quittable development requires "efficiency" and "equalization" of the use of all resources, both "efficiency" and "justice" cannot be applied or actualized without the supporting with moral dimensions in economic activities. Umer Chapra's thoughts are following: First, Efficiency, justice and morality. Second, the contributions of the state. Two thoughts on Islamic economic development below are known that the concept of Islamic economic development does not only measure the level of welfare in the world, but also the more important is how to prosper in the hereafter. The built concept of the two thinkers is directed more to the concept of empowerment or empowering natural resources efficiently and equitably by the role upholding ethical values and social justice.